2021
DOI: 10.1136/openhrt-2020-001485
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with severe aortic stenosis in the TAVI-era: how recent recommendations are translated into clinical practice

Abstract: ObjectiveApproximately 3.4% of adults aged >75 years suffer from aortic stenosis (AS). Guideline indications for aortic valve replacement (AVR) distinguish between patients with symptomatic and asymptomatic severe AS. The present analysis aims to assess contemporary practice in the treatment of severe AS across Europe and identify characteristics associated with treatment decisions, namely denial of AVR in symptomatic patients and assignment of asymptomatic patients to AVR.MethodsParticipants of the prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the overall analysis, the use of TAVI increased in all age groups between 2015 and 2019, including in patients aged <65 years. This might suggest that in some European countries, real-world clinical practice differs from the latest guideline recommendations, something which has been noted previously in Europe and the USA [50, 51]. However, there are various possible reasons for using TAVI in younger age groups, such as patients being high risk, patient preference, and an increasing level of surgical experience and availability of improved devices leading to younger high-risk patients being treated.…”
Section: Discussionmentioning
confidence: 94%
“…In the overall analysis, the use of TAVI increased in all age groups between 2015 and 2019, including in patients aged <65 years. This might suggest that in some European countries, real-world clinical practice differs from the latest guideline recommendations, something which has been noted previously in Europe and the USA [50, 51]. However, there are various possible reasons for using TAVI in younger age groups, such as patients being high risk, patient preference, and an increasing level of surgical experience and availability of improved devices leading to younger high-risk patients being treated.…”
Section: Discussionmentioning
confidence: 94%
“…Until comparable long-term durability is established, SAVR remains the first choice for lower-younger patients. Real-world data show that percutaneous techniques in the treatment of AS, an increasing number of patients are undergoing TAVR while asymptomatic 27…”
Section: Discussionmentioning
confidence: 99%
“…However, real-world data show that with the emergence of percutaneous techniques in the treatment of AS, an increasing number of patients are undergoing TAVR while asymptomatic. 67 A recent prospective multinational registry of patients with severe AS across Europe reported that, in the subgroup of 392 asymptomatic patients who were clinically evaluated to decide on treatment, AVR was decided on for 153 patients and, in 58% of cases, was performed percutaneously. 67 In that registry, up to 66 patients underwent TAVR while asymptomatic and having no formal indication according to current clinical guidelines.…”
Section: Role Of Transcatheter Aortic Valve Replacement In Asymptomat...mentioning
confidence: 99%
“…67 A recent prospective multinational registry of patients with severe AS across Europe reported that, in the subgroup of 392 asymptomatic patients who were clinically evaluated to decide on treatment, AVR was decided on for 153 patients and, in 58% of cases, was performed percutaneously. 67 In that registry, up to 66 patients underwent TAVR while asymptomatic and having no formal indication according to current clinical guidelines. As the technique improves and the complications of the procedure decrease, the indications for TAVR are expanding.…”
Section: Role Of Transcatheter Aortic Valve Replacement In Asymptomat...mentioning
confidence: 99%